Концепция развития филиала МГУ им. М.В. Ломоносова в городе Севастополе на период 2017–2020 годов - Danilchenko S. L. (Innovative trends of educational system development, 2017)
History of Branch - a consistent way of creating a sustainable open models of domestic higher education, historically proven professional effectiveness and relevance on the part of the individual, society and the state. Innovations born in the Branch of becoming tradition, became the ground for the next innovation.
Keywords: целевые ориентиры; современная миссия филиала; стратегические приоритеты филиала; перспективный облик филиала; Mission Branch The purpose and objectives of the Concept development Branch; The strategic priorities of the Branch targets the creation of new educational models Branch The mai; the future image of the Branch; Organizational conditions of the implementation of the Concept; цель концепции развития; задачи концепции развития; формирование образовательной модели; направления формирования модели; условия реализации концепции